Securing forests, development and interests : A governmentality analysis of the EU’s positions on REDD+ - Tähtö-Pakkanen, Mikko (My University, 2022)
In this thesis, I study the EU’s positions and views on how deforestation could be reduced in developing countries. I study this by analysing what kind of practices the EU sought to establish at the UNFCCC negotiations on REDD+ which took place from 2006 to 2014. The thesis relies on the theoretical framework provided by Foucauldian governmentality studies. I apply the idea of governmentality to study how the EU problematized deforestation, what kind of solutions it proposed and in relation to what goals. As a method, I apply Mithcell Dean’s analytics of government to study four aspects of governmentality: visibility, rationality, technologies of power and subjectivities. The main material consists of submissions the EU made at the REDD+ negotiations and a Commission communication on deforestation. I supplement these with other EU documents and texts. In addition to analysing the EU’s positions, I use previous governmentality research on REDD+ to outline the main debates and controversies of the REDD+ negotiations. These include attempts to modify the mechanism as well as arguments which rejected the rationality. The previous research has argued that a market rationality is dominant in REDD+ practices. My results show that the EU’s governmentality differed in many ways from the dominant rationality. The EU argued that lacking governance is the main driver of deforestation. It tried to connect REDD+ to a wider climate agreement and emphasized states’ responsibility in climate mitigation and its reconciliation with low-carbon development. Despite these significant differences, the EU supported REDD+ and tried to define the technical elements of the mechanism to enable governing according to its rationality. Previous governmentality research have missed these nuances in the EU’s rationality. Furthermore, there are similarities between the EU’s rationality, the proposal other actors made at the negotiations and how REDD+ has been implemented in some countries. Thus, future research could take another look at the negotiations to study whether the economic rationality really was as dominant as previous research has argued. Another direction would be to study the influence of different rationalities of current practices in the countries where REDD+ is being implemented.

Tässä tutkielmassa tutkin EU:n kantoja ja näkemyksiä siitä, miten kehitysmaiden metsäkatoa olisi mahdollistaa vähentää. Tarkemmin sanoen tutkin sitä, minkälaisia käytäntöjä EU kannatti metsäkadon vähentämiseksi osallistuessaan REDD+-mekanismia koskeviin neuvotteluihin kansainvälisissä ilmastoneuvotteluissa vuosina 2006–2014. Teoreettisena viitekehyksenä käytän foucault’laista hallintamentaliteettitutkimusta. Sen avulla tutkin, minkälaisena ongelmana EU hahmotti metsäkadon, minkälaisia ratkaisuja se ehdotti sille ja suhteessa mihin päämääriin. Käytän metodina Mitchell Deanin hallinnan analytiikkaa, joka auttaa operationalisoimaan hallintamentaliteetin neljän käsitteen kautta: näkymä, rationaliteetti, vallan teknologiat ja subjektiviteetit. Pääasiallisena aineistona käytän EU:n ilmastoneuvotteluissa tekemiä esityksiä sekä komission metsäkatoa käsittelevää komission tiedonantoa. Näiden lisäksi analyysia täydentävät muut EU:n julkaisemat dokumentit ja tekstit. EU:n kantojen lisäksi esittelen tutkielmassa aiempaan hallintamentaliteettitutkimukseen perustuen REDD+-neuvottelujen pääasialliset keskusteluaiheet ja kiistakohdat, mukaan lukien yritykset muokata mekanismin rationaliteettia tai kiistää sen toimivuus kokonaan. Aiempi tutkimus on katsonut markkinarationaliteetin hallitsevan REDD+-mekanismin käytäntöjä. Tulokseni osoittavat, että EU:n hallintamentaliteetti erosi monella tavalla vallitsevasta REDD+-rationaliteetista. EU piti metsäkadon pääasiallisena syynä huonoa hallintaa. Se pyrki myös yhdistämään REDD+:n vahvasti laajempaan ilmastosopimukseen ja korosti erityisesti valtioiden vastuuta sekä ilmastonmuutoksen torjunnassa että sen yhteensovittamisessa vähähiiliseen kehitykseen. Näistä eroavaisuuksista huolimatta EU kannatti REDD+ mekanismia ja pyrki määrittelemään mekanismin teknisiä elementtejä, siten, että ne mahdollistaisivat EU:n rationaliteetin mukaisen hallinnan. Aiempi hallintamentaliteettitutkimus ei ole huomioinut näitä EU:n rationaliteetin nyansseja. Muidenkin toimijoiden rationaliteeteissa sekä siinä, miten REDD+ on käytännössä toteutettu eri kehitysmaissa, on yhteneväisyyksiä EU:n kantoihin. Siksi jatkotutkimuksissa olisi syytä tarkastella uudelleen, kuinka hallitseva markkinarationaliteetti lopulta oli REDD+ neuvotteluissa, ja missä määrin erilaiset rationaliteetit vaikuttavat tämänhetkisissä REDD+:n toteutuksen käytännöissä.
Keywords: deforestation, climate change, REDD+, European Union, climate negotiations, international climate policy, international environmental policy, governmentality, analytics of government, metsäkato, ilmastonmuutos, REDD+, European Union, ilmastoneuvottelut, kansainvälinen ilmastopolitiikka, kansainvälinen ympäristöpolitiikka, hallintamentaliteetti, hallinnan analytiikka